2023
DOI: 10.14202/vetworld.2023.1-11
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of antibiotic resistance genes in Escherichia coli isolated from colibacillosis cases in broiler farms of Egypt

Abstract: Background and Aim: Multidrug resistance (MDR) of Escherichia coli has become an increasing concern in poultry farming worldwide. However, E. coli can accumulate resistance genes through gene transfer. The most problematic resistance mechanism in E. coli is the acquisition of genes encoding broad-spectrum β-lactamases, known as extended-spectrum β-lactamases, that confer resistance to broad-spectrum cephalosporins. Plasmid-mediated quinolone resistance genes (conferring resistance to quinolones) and mcr-1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 76 publications
0
8
1
Order By: Relevance
“…In contrast, high phenotypic resistance (100%) to CO was detected among APEC isolates from broiler chickens in India [ 49 ] and 33% in Qatar [ 45 ] which might be related to the use of CO on chicken farms as a therapeutic drug. In contrast to another study from Nepal [ 41 , 54 ] and Egypt [ 55 ], we found very low phenotypic resistance with a very low MIC 0.98 μg, which could be due to the ban of CO. CO should not be used for animal production because it is a last-resort antibiotic for human use. The Ministry of Agriculture and Livestock Development of Nepal has announced that there are no antibiotics in feed, and further monitoring and evaluation are needed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, high phenotypic resistance (100%) to CO was detected among APEC isolates from broiler chickens in India [ 49 ] and 33% in Qatar [ 45 ] which might be related to the use of CO on chicken farms as a therapeutic drug. In contrast to another study from Nepal [ 41 , 54 ] and Egypt [ 55 ], we found very low phenotypic resistance with a very low MIC 0.98 μg, which could be due to the ban of CO. CO should not be used for animal production because it is a last-resort antibiotic for human use. The Ministry of Agriculture and Livestock Development of Nepal has announced that there are no antibiotics in feed, and further monitoring and evaluation are needed.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 52 ], who reported a lower prevalence of the mcr1 ( 1.2%) with all isolates phenotypically R to CO [ 71 ]. Since the discovery of mcr1 in swine E. coli obtained from China [ 39 ], the relatively high mcr1 have been detected in several other studies of APEC isolates from broilers (43.9% [ 41 ], 22.8% [ 55 ] in Nepal, 15.3% [ 72 ] in China, and 64.3% [ 53 ] in Canada. The constant use of CO on poultry farms may be responsible for this alarming finding of a high percentage of mcr1 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antimicrobial-resistant bacteria in dairy products is recognized as a global problem of food safety and public health due to the potential transmission risk of resistant pathogens to the human population [ 18 , 19 ]. The resistance of E .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to traditional methods of microbiological cultivation based on morphological and biochemical characteristics, molecular biological methods have become a priority in the study of the Enterobacteriaceae family for species identification, epidemiological typing, and determination of a phylogenetic relationship between pathogenic and nonpathogenic bacteria. In addition, due to its practical significance, bacteria of this family can transfer and transmit genes of resistance to antibacterial drugs to other microorganisms in the human and animal gut microbiome [ 18 ]. At present, antibiotic resistance is recognized as a significant public health problem and poses a threat to human health [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance of E. coli infecting poultry has increased in recent decades, and antibiotic resistance has been changing in different parts of the world [ 14 , 41 ]. Such resistant E. coli could spread to humans through chicken meat consumption and noncompliance with hygiene practices among farmworkers [ 42 ]. This is particularly significant in underdeveloped countries, where antibiotic-treated meat or other animal products should be avoided [ 43 ].…”
Section: Discussionmentioning
confidence: 99%